Th22 cells and the intestinal mucosal barrier - Chen, Jieli; Yao, Jun (Frontiers in Immunology, 2023)
T-helper 22 (Th22) cells represent a novel subset of CD4+ T cells that exhibit distinctive characteristics, namely the secretion of IL-22 while abstaining from secreting IL-17 and interferon-γ (IFN-γ). These cells serve as the primary source of IL-22, and both Th22 cells and IL-22 are believed to play a role in maintaining intestinal mucosal homeostasis in inflammatory bowel disease (IBD). However, the precise functions of Th22 cells and IL-22 in this context remain a subject of debate. In this work, we aimed to elucidate their impact on the integrity of the intestinal mucosal barrier by presenting an overview of the molecular structure characteristics and functional effects of Th22 cells and IL-22. Furthermore, we would explore targeted treatment approaches and potential therapeutic strategies focusing on the Th22 and IL-22 pathways.